WEIT (What Element Is That?): Media Pembelajaran SPU Berbasis Indeks Card Match (ICM) guna Meningkatkan Hasil Belajar Peserta Didik SMA/MA - Zahra, Farah Rakhimy Az; Salsabila, Diva; Mahdiah, Munifa; Maharani, Windy; Fitri, Bali Yana (PAKAR Pendidikan, 2024)
Chemistry is a natural science discipline focusing on properties, structure, composition, chemical reactions. One of the studies on chemistry learning showed that more than 15.2% of students had difficulty memorising the elements in the periodic table. This is due to the many elements and ineffective learning methods. So, an interactive and fun learning method is needed. One of them is the WEIT (What Element Is That?) educational game, which is an innovation of the current game, Guess Who?. This research applies the R&D approach to the 4D development model and uses a quasi-experimental design. This research was conducted at SMAN 7 Padang, MAN 3 Padang City, & SMA Pembangunan Laboratorium Padang State University. The validity test obtained a validity value of 0.936 (valid category), with the results of the practicality test. The average value in the three schools is 0.955 (Very practical), 0.934 (Very practical), and 0.855 (Practical). In terms of effectiveness, the normality test was carried out with a p-value on the pretest of the experimental and control classes of 0.143 and 0.150, while on the post-test of the experimental and control classes were 0.149 and 0.168, indicating normally distributed data; t-test with a correlation value in the control class of 0.4221 (sufficient) and a very high value of 0.935 in the experimental class; finally the N-Gain test of the control and experimental classes was 50.07% (less effective) and 74.35% (effective), respectively. This indicates that WEIT games significantly improve students' learning outcomes on Periodic Table of Elements material. In addition, learner responses in the three schools showed a percentage of satisfaction, confirming that the WEIT game received a positive response from learners.